Feasibility and acceptability of a paeārahi (Indigenous Whānau Ora navigator) intervention for unintentional injury prevention for older Māori: non-randomised, non-comparator trial study protocol. Issue 6 (2nd September 2022) - Hikaka, Joanna; Ihimaera, Louise; Kool, Bridget; Kerse, Ngaire; Parsons, John; Maxwell-Crawford, Kirsty; Vercoe, Hariata; Merito, Parehuia; Cavadino, Alana; Te Ao, Braden; Aramoana-Arlidge, Brooke
Abstract : Background: Māori (the Indigenous population of Aotearoa New Zealand) experience increased burden of unintentional injury and reduced access to publicly funded injury prevention and rehabilitation services, compared with non-Māori. Māori-led models of care have been shown to improve outcomes for Māori. Paeārahi navigate across sectors (including health, education, housing and employment) to advocate for the best possible outcomes for individuals and families. This study aims to (1) test the acceptability and feasibility and (2) undertake exploratory efficacy analysis of a paeārahi injury intervention for Māori older adults. Methods: A prospective non-randomised, non-comparator study with preintervention and postintervention measurements of predefined outcomes. Eligible participants who consented to participate (Māori, 55+ years, community-dwelling and enrolled in one of three study general practices) will undergo a multivisit paeārahi intervention. The intervention includes home-hazard assessment, basic health screening, teaching of strength and balance exercises, education relating to injury prevention and access to injury-related, referral and connection to other health and social services) and participants can choose to have whānau (family) involved in the intervention. Outcomes: The primary outcome of interest is participant, whānau and paeārahi acceptability of the intervention. Secondary outcomes include intervention feasibility, cost-effectiveness and exploratory efficacy (including preintervention and postintervention unintentional injury-related hospitalisation, primary care access and public injury-related claims). Discussion: The findings of this intervention research will be used to inform injury care models for older Māori and process for Māori-led health intervention development more generally. Trial registration number: ACTRN12621001691831p.